TGFβ responsive tyrosine phosphatase promotes rheumatoid synovial fibroblast invasiveness. Issue 1 (6th November 2014) - Stanford, Stephanie M; Aleman Muench, German R; Bartok, Beatrix; Sacchetti, Cristiano; Kiosses, William B; Sharma, Jay; Maestre, Michael F; Bottini, Massimo; Mustelin, Tomas; Boyle, David L; Firestein, Gary S; Bottini, Nunzio
Abstract : Objective: In rheumatoid arthritis (RA), fibroblast-like synoviocytes (FLS) that line joint synovial membranes aggressively invade the extracellular matrix, destroying cartilage and bone. As signal transduction in FLS is mediated through multiple pathways involving protein tyrosine phosphorylation, we sought to identify protein tyrosine phosphatases (PTPs) regulating the invasiveness of RA FLS. We describe that the transmembrane receptor PTPκ (RPTPκ), encoded by the transforming growth factor (TGF) β-target gene, PTPRK, promotes RA FLS invasiveness. Methods: Gene expression was quantified by quantitative PCR. PTP knockdown was achieved using antisense oligonucleotides. FLS invasion and migration were assessed in transwell or spot assays. FLS spreading was assessed by immunofluorescence microscopy. Activation of signalling pathways was analysed by Western blotting of FLS lysates using phosphospecific antibodies. In vivo FLS invasiveness was assessed by intradermal implantation of FLS into nude mice. The RPTPκ substrate was identified by pull-down assays. Results: PTPRK expression was higher in FLS from patients with RA versus patients with osteoarthritis, resulting from increased TGFB1 expression in RA FLS. RPTPκ knockdown impaired RA FLS spreading, migration, invasiveness and responsiveness to platelet-derived growth factor, tumour necrosis factor and interleukin 1 stimulation. Furthermore, RPTPκ deficiency impaired the in vivo invasiveness of RA FLS. Molecular analysis revealed that RPTPκ promoted RA FLS migration by dephosphorylation of the inhibitory residue Y527 of SRC. Conclusions: By regulating phosphorylation of SRC, RPTPκ promotes the pathogenic action of RA FLS, mediating cross-activation of growth factor and inflammatory cytokine signalling by TGFβ in RA FLS.